O BRICS e o direito das cúpulas: a ordem mundial em transformação e os novos paradigmas jurídicos internacionais - Silva, Leiliane Rodrigues Corrêa (2015)
This work aims to analyze the existence of legal and economic world orders, through the historical perspective of the development of international law, based on the so-called Westphalian order for examining the Bretton Woods system. Furthermore aims to verify a possible transformation in these coordination systems coming from its incompleteness, especially with regard to the economic treatment and representation of developing countries, especially emerging denominated. Here represented by BRICS, which, given the scenario exposed by the twenty-first century global involvement of states, integration and interdependence in international relations, represent a new way of interaction between the emerging countries and promoting inter-regional multilateralism. Establishment of breaking paradigms and creation of international organizations through effective implementation of practice of a so-called "right of the domes." The research seeks to demonstrate the transformation of the international legal system in their practices, especially the customary review of the creation of an international paradigm in Post Modern right by the right of the domes.